A citação como recurso de afiliação acadêmica - Tatiana do Socorro Chaves Lima de Macedo (2006)
This dissertation presents a study of citations in academic writing from the perspective of citation analysis and the concept of genre (MORAVCSIK & MURUGESAN, 1975; THOMPSON & YIYUN, 1991; SWALES, 1986, 1990, 2004; BHATIA, 2004). The study focus on citations within the context of text production by expert and novice members ofthe Linguistics academic community and consisted in the comparative analysis of citations in nine research articles and thirteen papers dealing with Linguistics. The research articles were selected from issues published on-line in a Linguistics Journal, DELTA, between 1999 and 2004; the papers were the term papers (in this case, research projects on Linguistics) of thirteen students of a graduation program (mastersand doctors courses) in Brazil, 2004. The findings were compared in order to observe the differences and similarities of the occurrence of citations in both genres (research articles and term papers). These genres were chosen for two reasons: a) they are bound to the same discourse community and have characteristics in common; b) one of these genres, the research article, is recognized by the academic discourse community as an important means of communication and is regarded as an academic writing model. The results show that the linguistic choices that guide the writing of citations in the academicdiscourse community are shared by the expert members (authors of the research articles) and the novice ones (students of a graduation course). However, the novice members justification for the use of citations shows they are unaware of the reasons the academic discourse community urges the use of citations in written academic genres. The analysis also shows that some of the students who were participants of this studydo not recognize citations when they are written in the form of paraphrase. The conclusions of this study point to the need for a genre-based approach to discourse in English Language Teacher Education Programs aimed at developing students rhetorical consciousness about academic writing, and consequently about the use of citations in written texts, thereby building up an authorial positioning within their discourse community.